'I was just doing what a normal gay man would do, right?': The biopolitics of substance use and the mental health of sexual minority men. (September 2022) - Gaspar, Mark; Marshall, Zack; Adam, Barry D.; Brennan, David J.; Cox, Joseph; Lachowsky, Nathan; Lambert, Gilles; Moore, David; Hart, Trevor A.; Grace, Daniel
Drawing on 24 interviews conducted with gay, bisexual, queer and other men who have sex with men (GBM) living in Toronto, Canada, we examined how they are making sense of the relationship between their mental health and substance use. We draw from the literature on the biopolitics of substance use to document how GBM self-regulate and use alcohol and other drugs (AODC) as technologies of the self . Despite cultural understandings of substance use as integral to GBM communities and subjectivity, GBM can be ambivalent about their AODC. Participants discussed taking substances positively as a therapeutic mental health aid and negatively as being corrosive to their mental wellbeing. A fine line was communicated between substance use being self-productive or self-destructive. Some discussed having made 'problematic' or 'unhealthy' drug-taking decisions, while others presented themselves as self-controlled, responsible neoliberal actors doing 'what a normal gay man would do'. This ambivalence is related to the polarizing binary community and scientific discourses on substances (i.e. addiction/healthy use, irrational/rational, uncontrolled/controlled). Our findings add to the critical drug literature by demonstrating how reifying and/or dismantling the coherency of such substance use binaries can serve as a biopolitical site for some GBM to construct their identities and demonstrate healthy, 'responsible' subjectivity.